Geoekonomi Papua: Analisis Untung Rugi Akuisisi Saham Freeport - Adriani, Faradilla; W.S, Hawa Ridhani; A.R, Hendrina Nur (Global and Policy Journal of International Relations, 2021)
AbstractIn the Timika area, Papua, Indonesia has a Freeport mine which is one of the largest mines in the world. Freeport is managed by PT Freeport Indonesia, a mineral mining company which is an affiliate of Freeport-McMoRan and Mining Industry Indonesia (MIND ID). This mining company, which became the beginning of foreign investment in Indonesia, at the end of 2019, a 51.23% stake has officially become the owner of the Indonesian government. The acquisition of these shares is expected to be a new beginning for Indonesia to regain the 'rights' that should have been obtained long ago. In the acquisition of shares of 51%, observers have seen indications of losses in the success, so the authors are interested in examining how much the comparison of the profits obtained with the threat of future losses is. In this research method, the author uses a descriptive research method by analyzing the profit and loss of the acquisition of Freeport shares. The conclusion of the analysis states that Indonesia gains greater benefits from the threat of losses obtained after the acquisition of shares. Keywords: Freeport, Papua, Share Divestment, Share Acquisitions AbstrakDi daerah Timika, Papua, Indonesia memiliki tambang Freeport yang merupakan salah satu tambang terluas di dunia. Freeport dikelola oleh PT Freeport Indonesia, perusahaan tambang mineral yang merupakan hasil afiliasi dari Freeport-McMoRan dan Mining Industry Indonesia (MIND ID). Perusahaan tambang yang menjadi awal mula adanya investasi asing di Indonesia ini pada akhir tahun 2019, saham sebesar 51,23% telah resmi menjadi pemilik pemerintah Indonesia. Akuisisi saham ini diharapkan dapat menjadi awal baru bagi Indonesia untuk mendapatkan kembali ‘hak-hak’ yang semestinya bisa didapatkan sejak dulu. Dalam akuisisi saham sebesar 51%, para pengamat telah melihat adanya indikasi kerugian dalam keberhasilan tersebut, sehingga penulis tertarik untuk meneliti seberapa besar perbandingan keuntungan yang diperoleh dengan ancaman kerugian di masa depan. Dalam metode penelitian ini, penulis menggunakan metode penelitian deskriptif dengan menganalisis mengenai untung rugi akuisisi saham Freeport. Kesimpulan analisis tersebut menyatakan bahwa Indonesia mendapatkan keuntungan yang lebih besar dari ancaman kerugian yang didapat pasca akuisisi saham. Kata Kunci: Freeport, Papua, Divestasi Saham, Akuisisi Saham  DOI : https://doi.org/10.33005/jgp.v9i2.3009